Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cryst12010094
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progresses on Experimental Investigations of Topological and Dissipative Solitons in Liquid Crystals

Abstract: Solitons in liquid crystals have received increasing attention due to their importance in fundamental physical science and potential applications in various fields. The study of solitons in liquid crystals has been carried out for over five decades with various kinds of solitons being reported. Recently, a number of new types of solitons have been observed, among which, many of them exhibit intriguing dynamic behaviors. In this paper, we briefly review the recent progresses on experimental investigations of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 117 publications
0
7
0
Order By: Relevance
“…19 Since then, a number of directrons exhibiting intriguing dynamic behaviors have been generated and reported in both achiral and chiral nematics. 14–17,20–23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Since then, a number of directrons exhibiting intriguing dynamic behaviors have been generated and reported in both achiral and chiral nematics. 14–17,20–23…”
Section: Introductionmentioning
confidence: 99%
“…19 Since then, a number of directrons exhibiting intriguing dynamic behaviors have been generated and reported in both achiral and chiral nematics. [14][15][16][17][20][21][22][23] Directrons represent self-confined localized director oscillations that can propagate for a distance of at least the order of centimetres, limited by the cell size. As autonomous structures in electrically driven LCs, a wide range of novel and diverse applications for directrons have been proposed, including microcargo vehicles, 15,19,24 microreactors in chemical systems, 22 and logic devices for signal transduction 25 and even computation.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike a conservative soliton, a dissipative soliton is shaped not only by the balance of dispersion and nonlinearity but also by the balance of loss and gain. Consequently, dissipative solitons possess much more abundant shapes and dynamics, which have been extensively investigated in optical, chemical, biological, mechanical, and thermal systems. The importance of these studies is twofold.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was shown that domain walls could also be horizontally oriented, i.e., walls parallel to the surface of the LC cell. [5][6][7][8][9] Since the discovery of domain walls, topological defects have become a robust field of LC research, with extensive reviews, [10][11][12][13] in addition to the expansive field of LC display applications. [14][15][16][17][18][19][20][21][22][23] Domain walls have been shown to reduce into a pair of disclination lines at a critical field strength, in the pincement process.…”
Section: Introductionmentioning
confidence: 99%